Epitope-based vaccine as a universal vaccination strategy against Toxoplasma gondii infection: A mini-review - Hajissa, Khalid; Zakaria, Robaiza; Suppian, Rapeah; Mohamed, Zeehaida (Journal of Advanced Veterinary and Animal Research, 2019)
Despite the significant progress in the recent efforts toward developing an effective vaccine against toxoplasmosis, the search for new protective vaccination strategy still remains a challenge and elusive goal because it becomes the appropriate way to prevent the disease. Various experimental approaches in the past few years showed that developing a potential vaccine against the disease can be achievable. The combination of multi-epitopes expressing different stages of the parasite life cycle has become an optimal strategy for acquiring a potent, safe, and effective vaccine. Epitope-based vaccines have gained attention as alternative vaccine candidates due to their ability of inducing protective immune responses. This mini-review highlights the current status and the prospects of Toxoplasma gondii vaccine development along with the application of epitope-based vaccine in the future parasite immunization as a novel under development and evaluation strategy. J. Adv. Vet. Anim. Res., 6(2): 174-182, June 2019